Physicochemical Investigation of Some Oil Emulsions Oxidized by UV-B Radiation - Temel Kan Bakır; Hüseyin Kastrati (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the effects of UV B (50 µW/cm2) radiation at 306 nm on oil-in-water emulsions (O/W) using canola oil, soybean oil and linoleic acid were investigated. The oxidation rates of emulsions incubated at pH 7.0 and 37°C in the presence and absence of Cu (II) ions were determined by using iron (III) thiocyanate and thiobarbituric acid methods for the determination of primary and secondary products, respectively. The UV B-induced oxidation rates followed the order LA / Cu (II) > LA > Canola Oil / Cu (II) > Canola Oil > Soybean Oil / Cu (II) > Soybean Oil for both crops. Simultaneously, structural studies were performed using gas chromatography mass spectrometry (GC-MS). It was found that 18-carbon polyunsaturated fatty acid (PUFA) and monounsaturated fatty acid (MUFA) contents have an important role in canola and soybean oil oxidation. The unsaturated fatty acid contents of small carbon numbers increased for each emulsion sample, while the oxidation of fatty acid changes did not follow a regular order.